If you bite & devour one another : Biblical principles for handling conflict - Strauch, Alexander, 1944- (Lewis and Roth Publishers, 2011)
"Conflict in churches is a pervasive problem we know all too well. If You Bite & Devour One Another is the only book of its kind, examining all the biblical passages on conflict and outlining key scriptural principles for handling various kinds of conflicts among Christians--whether personal disputes, issues of Christian liberty in lifestyles, congregational matters, or disagreements about important doctrines. The book emphasizes Spirit-controlled attitudes and behaviors through solid Bible exposition and true-to-life stories of Christians handling real-life conflicts in a Christ-honoring way" -- BACK COVER.